2023
DOI: 10.1097/sla.0000000000006124
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Outcomes of Different Techniques for Gastric Ischemic Pre-Conditioning Before Esophagectomy

Alberto Aiolfi,
Davide Bona,
Gianluca Bonitta
et al.

Abstract: Background: Ischemia at the anastomotic site is a critical protagonist in the development of anastomosis-related complications after esophagectomy. Gastric ischemic conditioning (GIC) before esophagectomy has been described to improve the vascular perfusion at the tip of the gastric conduit with a potential effect on anastomotic leak (AL) and stenosis (AS) risk minimization. Laparoscopic (LapGIC) and angioembolization (AngioGIC) techniques have been reported. Purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…By evaluating surgeries that were completed minimally-invasively, rather than open, we may have inadvertently selected for less complex cases, although many variables suggest that these are complex patients (4.4% had undergone prior cardiothoracic surgery, 66.0% were clinical stage III, and 89.6% and 84.5% had received neoadjuvant chemotherapy and radiation, respectively). We also did not collect data on some technical factors that may impact complication rates and mortality, including intra-operative blood loss, ischemic preconditioning and anastomotic technique ( 23 , 24 ), nor did we include data on facility or surgeon MIE volume ( 25 ). However, a prior study in our health system demonstrated that regionalization of esophagectomy care to several Centers of Excellence was associated with decreased rates of complication, while surgeon and facility volume were not ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…By evaluating surgeries that were completed minimally-invasively, rather than open, we may have inadvertently selected for less complex cases, although many variables suggest that these are complex patients (4.4% had undergone prior cardiothoracic surgery, 66.0% were clinical stage III, and 89.6% and 84.5% had received neoadjuvant chemotherapy and radiation, respectively). We also did not collect data on some technical factors that may impact complication rates and mortality, including intra-operative blood loss, ischemic preconditioning and anastomotic technique ( 23 , 24 ), nor did we include data on facility or surgeon MIE volume ( 25 ). However, a prior study in our health system demonstrated that regionalization of esophagectomy care to several Centers of Excellence was associated with decreased rates of complication, while surgeon and facility volume were not ( 26 ).…”
Section: Discussionmentioning
confidence: 99%